Cardiac pacemaker–related endocarditis complicated with pulmonary embolism: Case report - Šačić, Dalila; Petrović, Olga; Zamaklar-Trifunović, Danijela; Ivanović, Branislava (Frontiers in Cardiovascular Medicine, 2023)
Cardiac device-related endocarditis as a device-therapy complication is a growing problem due to higher life expectancy and the increasing number of abandoned leads and subclinical symptoms. We reported a case of a 47-year-old woman with an implanted pacemaker who was admitted to the Clinic for cardiology due to the right-sided device-related infective endocarditis of the pacemaker leads with vegetations, mostly in the right atrium and right ventricle complicated by pulmonary embolism. She was diagnosed with systemic lupus erythematosus (SLE) several years after pacemaker implantation and was receiving immunosuppressive therapy. The patient was treated with prolonged intravenous antibiotic therapy. The extirpation of the atrial and ventricular lead was performed, and the posterior leaflet of the tricuspid valve was shaved.